Learning Co-Creation and Self-Determination: Lessons from Teaching Event Marketing - Vergara, Raymond Allan; Vergara, Kimberly Christie (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The role of learners in the learning process has increasingly evolved in the learning process, leaning towards a more active and participatory role in the learning process. The article explores the value of co-creation of learning and proposes that this value-in-use in the co-creation process is the learner’s intrinsic motivation. The study attempts to extend the self-determination theory by exploring learner experiences and presents a conceptual framework. The study finds that students that co-create their learning experiences in event marketing classes lead to self-motivation.